1993
DOI: 10.1002/jnr.490350210
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide induces calcium‐dependent release of [3H]dopamine release from striatal slices

Abstract: Hydroxylamine (0.01-30 mM), a nitric oxide (NO) generator, produced a concentration-dependent release of [3H]dopamine ([3H]DA) from rat striatal slices. Hemoglobin (10 microM), a NO scavenger, reduced basal [3H]DA release and blocked hydroxylamine (100 microM)-stimulated [3H]DA efflux. Tetrodotoxin (0.5 microM) had no significant effect. Sodium cyanide was used as a model compound to test the possibility that NO acted through blockade of mitochondrial electron transport. Calcium-free experimental buffer (1 mM … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
57
1
1

Year Published

1995
1995
2002
2002

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(64 citation statements)
references
References 18 publications
5
57
1
1
Order By: Relevance
“…Abnormalities in NO synthesis have been implicated in neurodevelopment and increasing the vulnerability to develop SCH (Akbarian et al 1993;Black et al 1999). Nitric oxide has been shown to increase the release of DA and influence the activity of the DA transporter in the striatum (Lonart et al 1993, Kiss et al 1999. It is possible that excessive NO synthesis might be involved in some more basic aspects of SCH along with contributing to the deficit in cortisol response to APO.…”
Section: Nitric Oxide and Apomorphinementioning
confidence: 99%
“…Abnormalities in NO synthesis have been implicated in neurodevelopment and increasing the vulnerability to develop SCH (Akbarian et al 1993;Black et al 1999). Nitric oxide has been shown to increase the release of DA and influence the activity of the DA transporter in the striatum (Lonart et al 1993, Kiss et al 1999. It is possible that excessive NO synthesis might be involved in some more basic aspects of SCH along with contributing to the deficit in cortisol response to APO.…”
Section: Nitric Oxide and Apomorphinementioning
confidence: 99%
“…However, there is confusion over the manner in which NO modulates dopamine release. In vitro studies using tissue slices have shown NO to increase dopamine efflux in the striatum (Lonart et al, 1993), whereas in vivo microdialysis studies using NO synthase inhibitors or exogenous NO suggest the opposite to be true (Guevara-Guzman et al, 1994;Rose et al, 1994b).…”
mentioning
confidence: 99%
“…First, nitric oxide is intimately connected with dopamine and glutamate, two neurotransmitter systems that are dysfunctional in schizophrenia (Lonart et al 1993;Montague et al 1994;Pogun et al 1994). Further, nitric oxide's dual action as mediator and negative modulator of glutamate neurotransmission at the NMDA receptor complex give this system a unique role in regulating the balance of excitatory and inhibitory influences.…”
Section: Discussionmentioning
confidence: 99%